Respuesta :

Answer:

I got 9

Step-by-step explanation:

Answer:

-3

Step-by-step explanation:

2x + 6 =

Simplifying

2x + 6 = 0

Reorder the terms:

6 + 2x = 0

Solving

6 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.

6 + -6 + 2x = 0 + -6

Combine like terms: 6 + -6 = 0

0 + 2x = 0 + -6

2x = 0 + -6

Combine like terms: 0 + -6 = -6

2x = -6

Divide each side by '2'.

x = -3

Simplifying

x = -3

ACCESS MORE